PENGARUH KOMPETENSI PROFESIONAL DAN KEDISIPLINAN TERHADAP KINERJA GURU DIMEDIASI MOTIVASI ( STUDI PADA GURU SMP NEGERI SE-KECAMATAN TAMAN KABUPATEN PEMALANG ) - Epi Azwatono, 12.5202.0171 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The general objective to be achieved in this research is to examine the professional competence and discipline against the performance of teacher motivation, while the goals are mediated in particular is a professional competence test influence of motivation, test the influence of the discipline of a professional test the motivation, competence of the teacher's performance, test the influence of discipline against the performance of teachers and test the effects of motivation on performance of teachers. This study examines the influence of professional competence and discipline on performance teacher mediated motivation. In this study involved 152 people respondents, all of whom is father/mother teacher PNS and GTT JUNIOR Country Se-Town garden, Pemalang. The benefits of this research there are two (2), namely: teoristis benefits can serve as a study material to enrich, broaden and deepen the concept and theory of professional competence, discipline, motivation and performance of teachers, while the practical benefits as 1. the Foundation for similar researchers with regard to professional competence, discipline, motivation and performance of teachers. 2. become inputs to the school, academia, Government, and education service district/city and Government in an attempt to improve the performance of teachers.Keywords: Kompetensi Profesional, discipline, motivasi and teacher performance.